Morrison, Angelou e Evaristo: mulheres negras e escrita revolucionária - Araújo, Eliza de Souza Silva (2021)
This research has as its main objective to present, from a comparative, interdisciplinary and transnational approach, an analysis of three narratives: The bluest eye (Toni Morrison), I know why the caged bird sings (Maya Angelou) and Becos da memória (ConceiçãoEvaristo). In these three literary texts, I observe that women writing narratives in the important historical moments that take place in the United States and Brazil when the books are launched, innovate in their handling of themes and also when it comes to emerging resources they articulate in the narrative form. Some of these narratological elements would be the jazz aesthetic (SMALL- MCCARTHY, 1995), rememory (MORRISON, 2019) and escrevivência, or, the writing of the lived experience (EVARISTO, 2005; 2007). Thus, I consider the writing of these black women as revolutionary from both an artistic and a political standpoint. While the narratives in question offer accounts on matters that were also explored by the black feminist agenda (in the United States and in Brazil), black feminism denounces the virtual absence of a discussion around the intersectional condition that affects black women even in feminist circles (CRENSHAW, 1989). Owing to historical records and analysis, as well as sociological and political ones about the Black Power Movement, the Black Arts Movement and the Movimento Negro Unificado, I provide a reading of the literary texts of the three authors of this corpus in dialogue and criticism of the praxis and ideologies of these movements. The narratives contemplated in this research not only introduce new perspectives in the political and artistic arenas, but also reinstate discussions about the literary canon, which claimed to be universal, questioning its historical erasures. With the analysis I articulate in this dissertation, rooted in interdisciplinary discussions with concepts from Literature, History, Sociology and Political Science, I aim to expand the comprehension of the dimensions of the black aesthetics in the U.S. and Brazilian contexts, while also highlighting how black women writing literature bring new dimensions and legacies to the universe of writing, knowledge and art, having historically fought for their own participation both in the literary and in the political space.